Identification by HPLC-MS of Anthocyanin Derivatives in Raisins - Ana Marquez; Montserrat Dueñas; María P. Serratosa; Julieta Merida (Journal of Chemistry)
The anthocyanin composition in red grapes dried under controlled conditions has been studied. Pyranoanthocyanins and condensed anthocyanins with flavanols by a methylmethine bridge have been identified. Typically, these compounds appear in wine after the fermentation process, as they require compounds such as pyruvic acid, acetoacetic acid, and acetaldehyde for their formation. During the chamber-drying process a stress situation is originated, inducing significant changes in the grape metabolism from aerobic to anaerobic, and as a result it produces the activation of the alcohol dehydrogenase enzyme (ADH) and others that would cause the formation of these compounds. These derivatives are very interesting because they give greater stability to the color of red wine.